HEAVY METAL ANALYSIS CO AND V ON SEDIMENT DISTRICT OF MAMUJU DISTRICT USING INDUCTIVELY COUPLED PLASMA OPTICAL EMISSION SPECTROSCOPY (ICP-OES) - Adji Permatasari; Maming Maming (Hasanuddin University, 2018)
This research concerning heavy metal analysis of Co and V on Mamuju Regency water sediments using Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES). Sediment sampling was conducted on four stations, namely the mouth of the Mamuju river, the mouth of the river Karema, the mouth of the river Rimuku, and front of Manakarra beach platform. The results showed that Co metes ranged from 0.167-0.208 mg/L while for metal V ranged from 0.649-0.944 mg/L. Of the three metals in the analysis are still below the threshold of metal quality standards in sediments or can be said not polluted.